Hukum Laut Internasional: Sebuah Hukum Progresif Terhadap Keimigrasian - S, Hendra; Priyo Amboro, Florianus Yudhi; Hutauruk, Rufinus Hotmaulana (Widya Yuridika, 2024)
The movement of people across countries has both positive and negative impacts on society. Globalization has changed the way humans move massively and quickly. Indonesia, as a country with a strategic geographical position between two continents and two oceans, plays a role as a center of human crossing. Indonesia's vast sea area is an important potential to be developed, and President Joko Widodo initiated the World Maritime Axis policy to drive the economy in the sea area. Government agencies in the sea area are part of the ecosystem that supports policies in the sea area. Policies related to law enforcement in the sea area continue to develop along with the expansion of activities at the border. Immigration has a strategic role because it regulates traffic at the state border, maintains state sovereignty, and supports the implementation of sea area policies. This research aims to evaluate the strategic role of immigration by applying a progressive legal theory approach and using normative legal research methods. Progressive law returns the law to its substantial purpose, so that legal changes should not eliminate the substance. This research aims to answer the challenges of the times by adapting the law in accordance with the purpose of the law. In the context of international law of the sea (UNCLOS 1982), this research looks at the strategic role of immigration in law enforcement in the sea area, including the territorial sea zone and additional sea zone. The cooperation of law enforcement agencies in the maritime area is key to maintaining state sovereignty and security at the border. This research contributes to the understanding of the strategic role of immigration in supporting Indonesia's territorial sea policy.